Removal of phosphate using chitosan-polymer composites. Issue 4 (December 2015) - Rajeswari, A.; Amalraj, Augustine; Pius, Anitha
Graphical abstract: Highlights: Removal of phosphate using PEG/chitosan & PVA/chitosan composites was investigated. Adsorption isotherms, kinetics, pH and contact time were examined. The optimum pH for phosphate ion adsorption was found to be 3. Q 0 values for PEG/chitosan and PVA/chitosan were found 74.9 and 46.2 mg g −1 . Both composites are promising materials for phosphate removal. Abstract: In the present study, removal of phosphate ions using polyethylene glycol/chitosan and polyvinyl alcohol/chitosan composites was investigated. The polyethylene glycol/chitosan and polyvinyl alcohol/chitosan composites were found to be effective for the removal of phosphate anions. The prepared adsorbents were characterized by scanning electron microscopy (SEM), energy dispersive analysis of X-rays (EDAX), Fourier transform infra-red (FTIR) and X-ray diffraction (XRD). The removal of phosphate has been found to be dependent on contact time and pH. Adsorption isotherm studies indicated that polymer composites satisfy Langmuir and Freundlich models. The rate of reaction follows pseudo-second-order kinetics. The results of the study indicated that polyethylene glycol/chitosan and polyvinyl alcohol/chitosan composites are useful materials for the removal of phosphate from aqueous solution.